Business Intelligence System for Decision Support for Motorcycle Loans: A Case Study, Ung Gui Heng Sakon Nakhon Co., Ltd. - Mahawong, Bhurich; Charoenrat, Jeeranan; Chongklaiklang, Rujira; Kuanhanghong, Amonrat; saensuk, mongkol (Journal of Engineering and Industrial Technology, Kalasin University, 2023)
The purpose of this research was to investigate the elements of business intelligence, with a particular focus on the elements of business intelligence that support loan managers' and employees' decision-making. It was created with the aid of a business intelligence program to aid in credit evaluation. Design a database management system with Microsoft SQL Server 2017 using the list of motorcycle loan rejections to be used by Ung Gui Heng Sakon Nakhon Co., Ltd. as an information system for credit consideration. According to the study and evaluation of 30 users' satisfaction, the use of business intelligence to support lending decisions was well received. The system has a mean of 3.67 and a standard deviation of 0.47, both of which are extremely high. The conclusion is that this business intelligence system is capable of analyzing data for decision-making and improvement. Enhance the efficiency with which credit service officers make credit decisions.